Crack Pipe Sharing in Context: How Sociostructural Factors Shape Risk Practices among Noninjection Drug Users. (December 2013) - Ivsins, Andrew; Roth, Eric; Benoit, Cecilia; Fischer, Benedikt
With the increasing prevalence of crack use in Canada in the previous decade, crack pipe sharing has emerged as a public health concern, implicated in the transmission of blood- and saliva-borne infections. Drawing on qualitative research with crack users in Victoria, Canada, participants' narratives of sharing pipes demonstrate how risk practices are shaped by social, structural, and environmental factors. Three main themes emerged: sharing pipes with friends and partners; economic motivations for sharing pipes; and the rules and etiquette of crack pipe sharing. Based on these themes we demonstrate that despite conventional views of drug equipment sharing as "bad behavior, " in the lived experience of our participants sharing pipes is a rational and functional activity. Ramifications of these findings are considered in light of future public health programs featuring the dissemination of health information and distribution of safer crack pipe kits.